Is it the right direction? The audit of business strategy - Kozák, Tamás (Applied Studies in Agribusiness and Commerce, 2012)
In the audit the process of strategic planning the management focuses the social expectations, threats and opportunities of the environment as well as the expectations of the owners. The main question is how much are the strategic tasks is matching with the environmental and corporate resources and capabilities. The answer which raised in strategy audit evaluates the ability to break the implementation barriers. A strategy is worth to realize only if we get satisfying answers to the questions related to the audit. A complex strategy audit method helps to appraise how the planning process is integrated.